2009
DOI: 10.1083/jcb.200809090
|View full text |Cite
|
Sign up to set email alerts
|

The mitotic spindle mediates inheritance of the Golgi ribbon structure

Abstract: The mammalian Golgi ribbon disassembles during mitosis and reforms in both daughter cells after division. Mitotic Golgi membranes concentrate around the spindle poles, suggesting that the spindle may control Golgi partitioning. To test this, cells were induced to divide asymmetrically with the entire spindle segregated into only one daughter cell. A ribbon reforms in the nucleated karyoplasts, whereas the Golgi stacks in the cytoplasts are scattered. However, the scattered Golgi stacks are polarized and transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 24 publications
3
57
0
7
Order By: Relevance
“…Specific isoforms of these kinases, MEK1b and ERK1c have also been found to reside in the Golgi and regulate its fragmentation during mitosis (16,17). These studies point to the role of the MEK/ERK pathway in remodeling the Golgi structure in response to mitogen signaling (42).…”
Section: Discussionmentioning
confidence: 83%
“…Specific isoforms of these kinases, MEK1b and ERK1c have also been found to reside in the Golgi and regulate its fragmentation during mitosis (16,17). These studies point to the role of the MEK/ERK pathway in remodeling the Golgi structure in response to mitogen signaling (42).…”
Section: Discussionmentioning
confidence: 83%
“…These events are most likely reversed as the organelle reforms during mitotic exit (Fig. 6) (Gaietta et al, 2006;Miller et al, 2009;Wei and Seemann, 2009) in a process that may also involve centrosome motility (Piel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism for organelle partitioning is transformation into vesicles that are dispersed throughout the cytoplasm. However, organelle inheritance is not only a stochastic process, but shares similarity with the ordered segregation of chromosomes that depends on the microtubule (MT)-based mitotic spindle (Shima et al, 1998;Jokitalo et al, 2001;Shorter and Warren, 2002;Wei and Seemann, 2009). Thus, breakdown of the NE does not involve vesiculation, but transfer of its components to the ER in a process that is linked to spindle formation (Ellenberg et al, 1997;Burke and Ellenberg, 2002;Puhka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cultured cells, the Golgi ribbon is fragmented into smaller pieces by the onset of mitosis (Rabouille and Jolo, 2003;Shima et al, 1998). Wei and Seemann reported that COPI vesicles accumulate around the centrosomes prior to anaphase initiation (Wei and Seemann, 2009). Moreover, the vesicles are transferred by the mitotic spindles during mitosis.…”
Section: Dependence Of Copi Vesicle Distribution On Astral Microtubulmentioning
confidence: 99%